Sufism And Quranic Interpretation: Bridging Spirituality, Culture, and Political Discourse in Muslim Societies - Ichwan, Moh. Nor; Ulama'i, A. Hasan Asy'ari; Masuwd, Mowafg Abrahem; Abdulghani, Naser Ali (Ulumuna, 2024)
This research discusses the influence of the Sufi interpretation of the Qur'an in shaping cultural narratives and political discourses in Muslim society. This study addresses the under-explored influence of Sufism beyond its spiritual domain, specifically in cultural and political spheres. This study aims to fill this void by exploring how the Sufi interpretation of the Qur'an influences contemporary cultural identity and political dynamics. The methods used in this study are multidisciplinary approaches, including analysis of Sufi literature, art, and social practices. The study's findings suggest that Sufism has a significant role in shaping cultural narratives, promoting tolerance and social justice, and providing a framework of thought that influences political discourse in Muslim communities. This study recommends that future studies focus more on Sufism's contribution to Islamic political thought and its relevance in the modern context. This research also emphasizes the importance of considering the spiritual dimension in analyzing cultural and political phenomena to understand the role of religion in shaping the social and political landscape more comprehensively.